2020
DOI: 10.1080/00016357.2020.1817545
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ multifaceted views of dental fear in a diagnostic interview

Abstract: Objectives: The aim was to examine how patients describe and perceive their dental fear (DF) in diagnostic interviews. Material and Methods: The sample consisted of dentally anxious patients according to the Modified Dental Anxiety Scale (MDAS), who had problems coping with conventional dental treatment. The voluntary participants (n ¼ 7, aged 31-62 years) attended a diagnostic interview aiming to map their DF before dental treatment. The data were analysed by theory-driven qualitative content analysis. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The relationship between DFA and dental attendance was examined in 57 articles ( n = 15 pediatric, n = 42 adult). The avoidance of or infrequent dental visits were linked with higher levels of DFA in children and adolescents [ 3 , 7 , 45 , 50 , 110 , 121 , 148 , 155 , 156 , 157 , 158 , 159 ] as well as adults [ 4 , 8 , 21 , 39 , 40 , 54 , 57 , 61 , 62 , 63 , 65 , 66 , 101 , 102 , 125 , 126 , 129 , 131 , 133 , 135 , 136 , 138 , 140 , 142 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Sporadic dental attendance as a child, compared to regular attendance, was associated with incre...…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between DFA and dental attendance was examined in 57 articles ( n = 15 pediatric, n = 42 adult). The avoidance of or infrequent dental visits were linked with higher levels of DFA in children and adolescents [ 3 , 7 , 45 , 50 , 110 , 121 , 148 , 155 , 156 , 157 , 158 , 159 ] as well as adults [ 4 , 8 , 21 , 39 , 40 , 54 , 57 , 61 , 62 , 63 , 65 , 66 , 101 , 102 , 125 , 126 , 129 , 131 , 133 , 135 , 136 , 138 , 140 , 142 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Sporadic dental attendance as a child, compared to regular attendance, was associated with incre...…”
Section: Resultsmentioning
confidence: 99%
“…The analyses revealed that suggestions for improving dental care were The study population was large enough for qualitative analysis, to achieve full saturation and to have individual authentic multiple citations in all subcategories, which increased the reliability (Kyngäs et al, 2000). It was also large in comparison with recent qualitative studies in a dental care setting (Damiano et al, 2019;Gulion & Vergnes, 2019;Kurki et al, 2021;Wang et al, 2017). All participants were over 15 years or adults.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the most feared situations or objects gained through the interview questionnaires and behavioral analysis guided the search for appropriate strategies for managing dental treatment and techniques to control the situation. Overall, the DI enabled us to address the most relevant emotional, behavioral, and physiological components of participants’ dental fear and anxiety 20 . The second goal was to increase the participants’ self‐efficacy.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the DI enabled us to address the most relevant emotional, behavioral, and physiological components of participants' dental fear and anxiety. 20 The second goal was to increase the participants' selfefficacy. A summary of the DI was provided to the participants.…”
Section: Interventionsmentioning
confidence: 99%